Surds and Indices
- Evaluate ( 0.00032)2/5
-
View Hint View Answer Discuss in Forum
Given that
(0.00032)2/5 = (32/100000)2/5
Solve the equation by algebra LawCorrect Option: D
Given that
(0.00032)2/5 = (32/100000)2/5
Solve the equation by algebra Law
= (25/105)2/5
= {(2/10)5}2/5
= (2/10)5x2/5
= (1/5)2 = 1/25
- If {(24)1/2}? = 256, find the value of '?'.
-
View Hint View Answer Discuss in Forum
Given that, (24x 1/2)? = 256
Apply the law of Fractional Exponents and Laws of Exponents
(am)n = am x n ----------------1
(am) x (an) = am + n-------------------2
am ÷ an = am ? n----------------3
and if pX = pY then X will be equal to Y. means X = Y;----------------4Correct Option: C
Given that, (24x 1/2)? = 256
Apply the law of Fractional Exponents and Laws of Exponents
⇒ (22)? = 28
⇒ 22 x ? = 28
⇒ 2 x ? = 8
∴ ? = 8/2 = 4
- If √10 + ∛ x = 4, then what is the value of x ?
-
View Hint View Answer Discuss in Forum
Given, √10 + ∛ x = 4
On squaring both sides,
After squaring the both sides,
Now, cubic on both sides,
Then solve the equation.Correct Option: B
Given, √10 + ∛ x = 4
On squaring both sides, we get
10 + ∛x = 16
⇒ ∛x = 6
Now, cubic on both sides, we get
x = (6)3 = 216
- Value of ? in expression
78.9 ÷ (343)1.7 x (49)4.8 = 7? is
-
View Hint View Answer Discuss in Forum
78.9 ÷ (343)1.7 x (49)4.8 = 7?
Apply the law of Fractional Exponents and Laws of Exponents
(am)(an) = am+n
am÷an=am?n
am/an=am?n
(am)n = amnCorrect Option: A
78.9 ÷ (343)1.7 x (49)4.8 = 7?
Apply the law of Fractional Exponents and Laws of Exponents
(am)(an) = am+n
am÷an=am?n
am/an=am?n
(am)n = amn
78.9 ÷ (343)1.7 x (49)4.8 = 7?
⇒ 78.9 ÷ (73)1.7 x (72)4.8 = 7?
⇒ 78.9 ÷ 75.1 x 79.6 = 7?
⇒ 78.9 - 5.1 + 9.6 = 7?
⇒ 718.5 - 5.1 = 7?
∴ ? = 13.4
- If a2x + 2 = 1,where a is a positive real number other than 1, then x = ?
-
View Hint View Answer Discuss in Forum
Given that, a2x + 2 = 1
Apply the algebra Law,
p0 = 1
and if
pX = pY
then X will be equal to Y. means X = Y;Correct Option: B
Given that, a2x + 2 = 1
Apply the algebra Law,
p0 = 1
⇒ a2x + 2 = a0
Apply the algebra law
pX = pY then X will be equal to Y. means X = Y;
⇒ 2x + 2 = 0
⇒ x = -2/2 = -1